Homozygous Gly530Ser substitution in COL5A1 causes mild classical Ehlers-Danlos syndrome - Giunta, Cecilia; Nuytinck, L.; Raghunath, Martin; Haußer-Siller, Ingrid; Paepe, A. de; Steinmann, Beat U. (American journal of medical genetics, 2002)
Skin hyperelasticity, tissue fragility with atrophic scars, and joint hypermobility are characteristic for the classical type of Ehlers-Danlos syndrome (EDS). The disease is usually inherited as an autosomal dominant trait; however, recessive mode of inheritance has been documented in tenascin-X-deficient EDS patients. Mutations in the genes coding for collagen α1(V) chain (COL5A1), collagen α2(V) chain (COL5A2), tenascin-X (TNX), and collagen α1(I) chain (COL1A1) have been characterized in patients with classical EDS, thus confirming the suspected genetic heterogeneity. Recently, we described a patient with severe classical EDS due to a Gly1489Glu substitution in the α1(V) triple-helical domain who was, in addition, heterozygous for a disease-modifying Gly530Ser substitution in the α1(V) NH2-terminal domain [Giunta and Steinmann, 2000: Am. J. Med. Genet. 90:72-79; Steinmann and Giunta, 2000: Am. J. Med. Genet. 93:342]. Here, we report on a 4-year-old boy with mild classical EDS, born to healthy consanguineous Turkish parents; the mother presented a soft skin, while the father had a normal thick skin. Ultrastructural analysis of the dermis revealed in the patient the typical “cauliflower” collagen fibrils, while in both parents variable moderate aberrations were seen. Mutation revealed the presence of a homozygous Gly530Ser substitution in the α1(V) collagen chains in the patient, while both parents were heterozygous for the same substitution. An additional mutation in either the COL5A1 and COL5A2 genes was excluded. Furthermore, haplotype analysis with polymorphic microsatellite markers excluded linkage to the genes coding for α3(V) collagen (COL5A3), tenascin-X (TNX), thrombospondin-2 (THBS2), and decorin (DCN). These new findings support further our previous hypothesis that the heterozygous Gly530Ser substitution is disease modifying and now suggest that in the homozygous state it is disease causing. © 2002 Wiley-Liss, Inc.
Gesehen am 01.04.2021